Health Education Intervention as an Effective Means for Prevention of Respiratory Infections Among Hajj Pilgrims: A Review - Goni, Mohammed Dauda; Hasan, Habsah; Wan-Arfah, Nadiah; Naing, Nyi Nyi; Deris, Zakuan Zainy; Arifin, Wan Nor; Baaba, Aisha Abubakar; Aliyu, Abdulwahab; Adam, Babagana Mohammed (Frontiers in Public Health, 2020)
The prevalence of respiratory illness has continued to surge among Hajj pilgrims from different countries despite having some practices of preventive measures. Respiratory illnesses during Hajj could be due to many reasons and many factors that promote disease spread. These factors include overcrowding, cigarette smoking, and direct contact with infectious agents particularly viruses promote the spread of respiratory infections. However, due to the longer duration of the pilgrimage, there are high chances of pilgrims contracting various respiratory illnesses due to exposure to respiratory pathogens. Hajj pilgrims' knowledge, attitudes, and practices toward respiratory tract infections are used as the determinant of the effectiveness of the health education interventions. Knowledge and application of basic hygiene principles, use of face masks, following cough etiquettes, engaging in social distancing, and engaging in other measures are highly important. In this paper, we reviewed the various effective intervention strategies implemented to help prevent respiratory tract infections during Hajj.